2016
DOI: 10.3111/13696998.2016.1158718
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimization analysis of sublingual immunotherapy versus subcutaneous immunotherapy for house dust mite respiratory allergic disease in Denmark

Abstract: Objectives Currently, patients with persistent moderate-to-severe house dust mite (HDM) allergic rhinitis despite use of symptom-relieving medication can be offered subcutaneously administered allergy immunotherapy (SQ SCIT; Alutard SQ) as standard care of treatment in Denmark. Recently, a HDM sublingually administered allergy immunotherapy tablet (SQ SLIT-tablet; ACARIZAX) has been developed for at-home treatment. The purpose of this analysis is to compare the costs related to treatment and administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…this assumption is a limitation of this analysis. However, a CMA was determined to be the most feasible and appropriate type of economic analysis, as this assessment method has also been used in similar studies [34][35][36]. Costs and resource use included in the analysis were solely associated with the treatments and treatment administration, including direct and indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…this assumption is a limitation of this analysis. However, a CMA was determined to be the most feasible and appropriate type of economic analysis, as this assessment method has also been used in similar studies [34][35][36]. Costs and resource use included in the analysis were solely associated with the treatments and treatment administration, including direct and indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…Among treatment options for AR, AIT (that includes SCIT and SLIT) has exclusive features, that include the ability to alter the natural history of allergy and to extend its effectiveness, differently from drug treatment, to several years after discontinuing the therapy. A growing bulk of data indicates that SCIT and SLIT may be very advantageous to the healthcare systems [3538]. However, the pharmacoeconomic advantage demonstrated in optimally performed studies needs to be confirmed by real-life experiences.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Previous economic comparisons of SCIT and SLIT‐tablets for individuals with allergies to other allergens have also been conducted as cost‐minimization analyses. 25 , 26 …”
Section: Methodsmentioning
confidence: 99%